Quantitative evaluation of anti-sliding performance and dosage regulation of steel slag asphalt mixture facing service environment - Zhiqiao Cheng; Ping Li; Jingsheng Pan (PLoS ONE, 2026)
In view of the practical demands for quantitative evaluation on skid resistance and scientific regulation of steel slag content of steel slag asphalt mixtures under service conditions, this study takes steel slag content, temperature and abrasion effect as research factors. Via accelerated loading abrasion tests, this paper investigates the evolution characteristics and quantitative evaluation models of two core skid resistance indicators namely British Pendulum Number (BPN) and Mean Texture Depth (MTD) under three steel slag contents and three temperature gradients. The results show that both BPN and MTD values of steel slag asphalt mixtures decrease obviously with the increase of abrasion cycles. High temperature can significantly accelerate the deterioration of skid resistance, which provides important experimental references for the optimization and regulation of steel slag content in service areas with different temperatures. BPN and MPN present generally high correlation under various temperatures and steel slag contents, which verifies the coordinated variation rule of the two skid resistance indicators under multi-factor conditions. From the perspective of staged abrasion degradation, the abrasion evolution processes of BPN and MTD can be clearly divided into low, medium and high abrasion stages. Their correlations differ greatly in different stages, laying a solid foundation for segmented prediction of skid resistance service life. The research findings further improve the quantitative evaluation system for skid resistance of steel slag asphalt mixtures oriented to actual service environment, and offer accurate data support and practical guidance for scientific adjustment of steel slag content in practical engineering.